Hubungan Antara Kondisi Fisik Rumah Dan Perilaku Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Sangkrah Kota Surakarta Tahun 2016 - Susanti, Lusy Ika, Dwi Astuti, SKM,M.Kes, Sri Darnoto, SKM, MPH (2016)
Pulmonary tuberculosis is still a major public health problem. Its caused by demographic factors and environmental factors. This research determines correlation between physical condition of house and behaviour with occurence of pulmonary tuberculosis in work area of public health center in Sangkrah, Surakarta. This research applied observational methods with case control design. The population were society in work area public health center in Sangkrah. Sampling technique applied purposive sampling and taken as many as 42 respondents. Statistical test using chi square with help of computer program, with a significant level of 0,05. To estimate the risk using odd ratio. The results showed were significant correlation between floor types (p-value = 0,024), bedroom window (p-value = 0,031), and natural lighting (p-value = 0,002) with occurence of pulmonary tuberculosis. No correlation between house ventilation (p-value = 0,121), house temperature (p-value = 0,212), house humidity (p-value = 0,095), density residential (p-value = 495), the act of open the window (p-value = 0,064), and behavior spit (p-value = 1,000).